Strategi Pengelolaan Kawasan Objek Wisata Air Terjun Pung Bunga Kabupaten Maros - Juanda, Muhammad Faisal; Haris, Nurul Afdal; Bure, Lisye Marselina; Mulyani, Sri (LaGeografia, 2024)
Waterfall attractions and natural bathing are two types of tourism activity currently favored by the community. Pung Bunga Waterfall is located in Maros Regency This research aims to formulate a strategy for managing the Pung Bunga Waterfall tourist attraction area in Maros Regency. The type of research conducted is a mixed method of quantitative and qualitative. Data collection techniques are surveys, observations, interviews, and documentation. Data analysis techniques using the SWOT method to later produce several alternative strategies in managing the research location. The use of the SWOT analysis method to describe Strengths (Strengths), Weaknesses (Weaknesses), Opportunities (Opportunities), and Threats (Threats). After that, scoring is carried out to determine the strategy that can be used. The results of the research obtained are 4 management strategies including (1) Management of tourist attraction areas in a sustainable and integrated manner by maintaining waterfall attractions as the main tourist attraction. (2) Cooperate with various parties such as the government, private sector, and environmentalists to develop complex, superior, and highly competitive tourist areas. (3) Maintain the sustainability and naturalness of the area by maintaining environmental conditions and educating visitors on the importance of forests and waters to hook visitors who come. (4) Involving the local community in POKDARIWIS and promotion in the context of managing the tourist attraction area.AbstrakObjek wisata air terjun dan permandian alam  adalah salah satu jenis kegiatan pariwisata yang saat ini banyak digemari oleh masyarakat. Air terjun Pung bunga terdapat di Kabupaten Maros  Penelitian ini bertujuan untuk merumuskan strategi untuk pengelolaan kawasan objek wisata air terjun Pung Bunga di Kabupaten Maros. Jenis penelitian yang dilakukan adalah metode campuran kuantitatif dan kualitatif. Teknik Pengumpulan data yaitu survei, observasi, wawancara dan dokumentasi. Teknik Analisis data dengan menggunakan metode SWOT agar nantinya menghasilkan beberapa alternatif strategi dalam pengelolaan lokasi penelitian. Penggunaan metode analisis SWOT agar dapat menguraikan Kekuatan (Strenght), Kelemahan (Weakness), Peluang (Opportunity) dan Ancaman (Threat). Setelah itu dilakukan skoring dalam penentuan strategi yang dapat digunakan. Adapun hasil penelitian yang diperoleh yaitu 4 strategi pengelolaan diantaranya (1) Pengelolaan Kawasan Objek wisata secara berkelanjutan dan terpadu dengan mempertahankan atraksi air terjun sebagai objek wisata utama. (2) Melakukan kerja sama dengan berbagai pihak seperti pemerintah, swasta maupun pemerhati lingkungan untuk mengembangkan kawasan wisata yang kompleks, unggul serta berdaya saing tinggi. (3) Menjaga kelestarian dan kealamian kawasan dengan mempertahankan kondisi lingkungan dan edukasi bagi pengunjung pentingnya hutan dan perairan sehingga mengait pengunjung yang datang. (4) Pelibatan masyarakat setempat dalam POKDARIWIS dan promosi dalam rangka pengelolaan kawasan objek wisata.